2015
DOI: 10.1089/scd.2014.0380
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Differentiation of Endogenous Stem Cells: Therapeutic Effect from Icariside II on a Rat Model of Postprostatectomy Erectile Dysfunction

Abstract: Self-renewal and differentiation of endogenous stem cells (SCs) are essential for adult tissue homoeostasis and intrinsic healing capacity. In this study, we hypothesize that penis contains a small population of endogenous SCs, which might help rejuvenation of damaged erectile function. In this study, 60 newborn male rats were intraperitoneally injected with 5-ethynyl-2-deoxyuridine (EdU; 50 mg/kg) for the purpose of tracking endogenous SCs. Twelve weeks later, 48 rats underwent bilateral cavernous nerves inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Our previous works have demonstrated that penis contains small populations of endogenous SCs by LRC strategy Xu et al, 2015) . Stem/progenitor cells, residing in various types of organs, play a critical role in homeostasis and wound repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous works have demonstrated that penis contains small populations of endogenous SCs by LRC strategy Xu et al, 2015) . Stem/progenitor cells, residing in various types of organs, play a critical role in homeostasis and wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…These label retaining cells (LRC) are generally considered as putative SCs because of their asymmetric division, slow-cycling and quiescent features. Our previous works have demonstrated that penis contains small populations of endogenous SCs by LRC strategy Xu et al, 2015) . Schwann cells, the ensheathing glial cells of the peripheral nerve system, are crucial for normal nerve function and for nerve repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have highlighted the therapeutic potential of, and the underlying mechanism for, the involvement of endogenous stem cells (SCs) in these two treatments. Rats that underwent injection of EdU for the purpose of tracking endogenous SCs at birth and management of BCNI or pelvic neurovascular injury at 12 weeks were treated with the antioxidant agent icariside II (Xu et al ., ) or Li‐ESWT (Li et al ., ). Both the studies reported erectile dysfunction improvement, tissue restoration and more endogenous EdU (+) SCs recruited to the damaged penile areas, implying the probability of self‐healing by endogenous SC mobilization and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al activated the p38 mitogen-activated protein kinase (MAPK) pathway to stimulate endogenous stem cells. 60 The p38 MAPK pathway is thought to be integral in stem cell activation and differentiation and as such may serve alongside LESWT as another means of activating these endogenous cells.…”
Section: Endogenous Stem Cellsmentioning
confidence: 99%